The role of microtransactions in impulse buying and purchase intention in the video game market - Rita, Paulo (2024)
Rita, P., Guerreiro, J., Ramos, R., & Caetano, R. G. (2024). The role of microtransactions in impulse buying and purchase intention in the video game market. Entertainment Computing, 50, 1-8. Article 100693. https://doi.org/10.1016/j.entcom.2024.100 --- Paulo Rita was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia) under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.